On the provenance of GEMS, a quarter century post discovery. (15th October 2022) - Bradley, John P.; Ishii, Hope A.; Bustillo, Karen; Ciston, James; Ogliore, Ryan; Stephan, Thomas; Brownlee, Donald E.; Joswiak, David J.
Abstract: The provenance of GEMS (glass with embedded metal and sulfides) in cometary type interplanetary dust particles is investigated using analytical scanning transmission electron microscopy and secondary ion mass spectrometry. We review the current state of knowledge and closely examine the densities, elemental compositions and distributions, iron oxidation states, and isotopic compositions of a subset of GEMS in chondritic porous interplanetary dust. We find that GEMS are underdense with estimated densities that are 35–65% of compositionally equivalent crystalline aggregates. GEMS low densities result in a lower contribution to the bulk compositions of IDPs than has been assumed based on their volume fraction. We also find that element/Si ratios, assumed to be primary (indigenous), are instead perturbed by contamination and secondary alteration, including pulse heating during atmospheric entry. Fe in pyrrhotite inclusions was oxidized and Mg, S, Ca, and Fe were depleted relative to lithophile Al and Si, resulting in reduction in element/Si ratios. Because they trap outgassing elements, Fe-rich oxide rims that formed on the surface of GEMS are serendipitous "witness plates" to the changes in composition that accompany atmospheric entry. As a result of alteration, GEMS elemental compositions cannot reliably inform about their provenance. Except for highly anomalous oxygen isotope ratios measured in some large GEMS grains that indicate a contribution from circumstellar dust, oxygen isotope compositions are generally poor indicators of provenance. Prior work indicates that most GEMS fall close to the terrestrial oxygen isotope composition, which, however, does not exclude a presolar interstellar origin. Nitrogen isotopic compositions are more diagnostic. Elevated 15 N/ 14 N ratios indicate that GEMS accreted in conjunction with formation of organic matter by ion–molecule reactions in a cold (<50 K) presolar environment like the extreme outer nebula or interstellar medium. Considering all observations, we conclude that GEMS are most likely processed interstellar silicates.